2020
DOI: 10.3390/cancers12061464
|View full text |Cite
|
Sign up to set email alerts
|

The miR-26b-5p/KPNA2 Axis Is an Important Regulator of Burkitt Lymphoma Cell Growth

Abstract: The expression of several microRNAs (miRNAs) is known to be changed in Burkitt lymphoma (BL), compared to its normal counterparts. Although for some miRNAs, a role in BL was demonstrated, for most of them, their function is unclear. In this study, we aimed to identify miRNAs that control BL cell growth. Two BL cell lines were infected with lentiviral pools containing either 58 miRNA inhibitors or 44 miRNA overexpression constructs. Eighteen constructs showed significant changes in abundance over time, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
3
16
0
Order By: Relevance
“…In the last decade, several studies have identified miR-26b-5p to be crucial in the development and progression of cancers. As reported, miR-26b-5p is a tumor suppressor and modulator in cell cycle regulation that targets different genes, including CCND2, PLOD2, JAG1, MAP3K9 and KPN2 [ 6 , 8 , 23–25 ]. Notably, the ceRNA hypothesis sparked another miRNA-mediated mechanism, in which miRNA acts as the key modulator linking competing endogenous RNAs, including long non-coding RNA (lncRNA), circular RNA (circRNA), pseudogenes and protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, several studies have identified miR-26b-5p to be crucial in the development and progression of cancers. As reported, miR-26b-5p is a tumor suppressor and modulator in cell cycle regulation that targets different genes, including CCND2, PLOD2, JAG1, MAP3K9 and KPN2 [ 6 , 8 , 23–25 ]. Notably, the ceRNA hypothesis sparked another miRNA-mediated mechanism, in which miRNA acts as the key modulator linking competing endogenous RNAs, including long non-coding RNA (lncRNA), circular RNA (circRNA), pseudogenes and protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-26b-5p inhibites cell proliferation and induces apoptosis in multiple myeloma cells by targeting JAG1, and maintains the stemness of hepatocellular carcinoma cells by inhibiting HSC71/HSPA8. miR-26b-5p inhibition promoted the growth of Burkitt lymphoma cells by repressing the KPNA2 expression [ 8 ]. Additionally, miR-26b-5p upregulation restricted the malignant features of human apillary thyroid cancer by degrading beta-catenin [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…MRPL15 is a member of MRPL, which provides energy in the form of ATP for cell growth. MRPL15 has been reported to have a predictive value in breast cancer metastasis (19) and can promote Burkitt lymphoma growth (20). Little research has reported the predictive value of MRPL15 in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have determined that KPNA2 is associated with modulating both the nuclear import and the cytoplasm export of molecules [ 4 , 9 , 20 ]. Recently, higher expression of KPNA2 was demonstrated in breast cancer [ 8 ], burkitt lymphoma [ 23 ], melanoma [ 33 ], bladder cancer [ 25 ], and correlated with the poor prognosis of patients. However, the exact role of KPNA2 in ovarian cancer and its underlying molecular mechanism have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%